Uncovering the pathways underlying whole body regeneration in a chordate model, Botrylloides leachi using de novo transcriptome analysis - Zondag, Lisa E (BMC Genomics, 2016)
BACKGROUND: Regenerative capacity differs greatly between animals. In vertebrates regenerative abilities are highly limited and tissue or organ specific. However the closest related chordate to the vertebrate clade, Botrylloides leachi, can undergo whole body regeneration (WBR). Therefore, research on WBR in B. leachi has focused on pathways known to be important for regeneration in vertebrates. To obtain a comprehensive vision of this unique process we have carried out the first de novo transcriptome sequencing for multiple stages of WBR occurring in B. leachi. The identified changes in gene expression during B. leachi WBR offer novel insights into this remarkable ability to regenerate. RESULTS: The transcriptome of B. leachi tissue undergoing WBR were analysed using differential gene expression, gene ontology and pathway analyses. We observed up-regulation in the expression of genes involved in wound healing and known developmental pathways including WNT, TGF-β and Notch, during the earliest stages of WBR. Later in WBR, the expression patterns in several pathways required for protein synthesis, biogenesis and the organisation of cellular components were up-regulated. CONCLUSIONS: While the genes expressed early on are characteristic of a necessary wound healing response to an otherwise lethal injury, the subsequent vast increase in protein synthesis conceivably sustains the reestablishment of the tissue complexity and body axis polarity within the regenerating zooid. We have, for the first time, provided a global overview of the genes and their corresponding pathways that are modulated during WBR in B. leachi. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12864-016-2435-6) contains supplementary material, which is available to authorized users.